Abundance and Potential of Asteroidea as Bioindicator of Lead (Pb) in the Coastal Zone at Bangkalan Regency, Madura - Kurniawati, Yusfita; Maramis, Arnetta Yolanda; Mudloifah, Istatik; Rahayu, Dwi Anggorowati (Biotropika: Journal of Tropical Biology, 2023)
Asteroidea is a marine invertebrate that has a role as a bioindicator, but the research related to the abundance and potential of Asteroidea as a bioindicator of lead on Madura Island is not to be done. This study aimed to analyse the effect of Pb concentration on Asteroidea population density in Bangkalan Regency. For collecting data, the transect plotting method with a plot measuring 1x1 m2 with 30 plots in the intertidal zone. Seawater sampling was divided into three stations, such as station I-0 meters (edge), station II-50 meters (middle) and station III-100 meters (deep zone), then the seawater samples were tested for lead Pb levels using the AAS method (atomic absorption spectrophotometer). Data analysis was carried out with quantitative descriptive with Asteroidea composition including diversity index, relative density and dominance index as parameters. The results obtained were sea star species, Cryptasterina sp. and Aquilonastra coronata, with a diversity index value of 0, a relative density of 100% and a dominance index of 1. The results for Pb concentration on Tengket Beach at a depth of 0 meters, 50 meters and 100 are 0.072 ppm; 0.16 ppm; 0.61 ppm and Pantai Modung at 0.5 ppm; 0.83 ppm; 0.82 ppm. Based on the analysis of the abundance of Asteroidea, the higher the concentration of Pb contained in the waters, the lower the density of Asteroidea. It was concluded that there was no relationship between Pb concentrations in seawater and sea star population density, found a high lead metal yield on the diversity and abundance of sea stars.